Abundance and physiology of dominant soft corals linked to water quality in Jakarta Bay, Indonesia - Gunilla Baum; Indra Januar; Sebastian C.A. Ferse; Christian Wild; Andreas Kunzmann (PeerJ, 2016)
Declining water quality is one of the main reasons of coral reef degradation in the Thousand Islands off the megacity Jakarta, Indonesia. Shifts in benthic community composition to higher soft coral abundances have been reported for many degraded reefs throughout the Indo-Pacific. However, it is not clear to what extent soft coral abundance and physiology are influenced by water quality. In this study, live benthic cover and water quality (i.e. dissolved inorganic nutrients (DIN), turbidity (NTU), and sedimentation) were assessed at three sites (< 20 km north of Jakarta) in Jakarta Bay (JB) and five sites along the outer Thousand Islands (20–60 km north of Jakarta). This was supplemented by measurements of photosynthetic yield and, for the first time, respiratory electron transport system (ETS) activity of two dominant soft coral genera, Sarcophyton spp. and Nephthea spp. Findings revealed highly eutrophic water conditions in JB compared to the outer Thousand Islands, with 44% higher DIN load (7.65 μM/L), 67% higher NTU (1.49 NTU) and 47% higher sedimentation rate (30.4 g m−2 d−1). Soft corals were the dominant type of coral cover within the bay (2.4% hard and 12.8% soft coral cover) compared to the outer Thousand Islands (28.3% hard and 6.9% soft coral cover). Soft coral abundances, photosynthetic yield, and ETS activity were highly correlated with key water quality parameters, particularly DIN and sedimentation rates. The findings suggest water quality controls the relative abundance and physiology of dominant soft corals in JB and may thus contribute to phase shifts from hard to soft coral dominance, highlighting the need to better manage water quality in order to prevent or reverse phase shifts.